“Da imprensa especial” à imprensa espírita: um estudo da Revista Espírita (1858-1868) - Wolf, Rayssa Almeida (2017)
This work aims to present a study of the constitution of the Spiritist Press through the analysis of the Spiritist Magazine (Revue Spirite), in the period in which the French pedagogue Hippolyte Léon Denizard Rivail under the pseudonym Allan Kardec coordinated the edition of the Magazine, 1858-1868. The relevance of this periodical and of the Parisian Society for Spiritist Studies in the formation of French spiritualism during the middle of the nineteenth century, and especially in the construction of models of magazines and spiritist societies, which found fertile ground in Brazil. The research is based on the French cultural context of printed production, which seeks to present the evolution of booksellers and printers and the cultural revolution that these transformations in the way individuals deal with books and reading, provided to society. In this sense, we argue that the Parisian Society of Spiritist Studies and the Spiritist Magazine are two intrinsic elements for understanding not only the configuration of the press and the current spiritist editorial market, but essential for understanding spiritism in its breadth. The theoretical-methodological tools that guided the reading of the Spiritist Magazine were the reflections on Content Analysis and Umberto Eco. Not to mention the specific bibliographies that thematically relate the relations of spiritism to the printed culture. This dissertation was organized in three chapters, in which a collection of the elements that involve spiritism and the printed culture is realized. In a second moment, I present the constitution and the position of the Parisian Society of Spiritist Studies in and in relation to the Spiritist Magazine. Finally, we dedicate ourselves to an editorial profile of the Journal and to show which press it was organized by a writer, who dedicated himself to describing supernatural phenomena and publishing them in the form of books and magazines. Thus, in a religion of the book, of reading and of a magazine.